Relação entre dieta e morfologia da cavidade oral de girinos (AMPHIBIA: ANURA) - Silva, Larissa Souza (2022)
Filter animals are aquatic, planktonic or benthic, freshwater or marine and encompass unicellular and multicellular organisms. Associated with this diversity, animals using filter feeding mechanisms have adapted structures to food collection. The most anuran species have filter feeding tadpoles, adopting herbivorous diet, consisting of different algae. The modes of food capture that tadpoles employ and the variety of diet are related to variations in the external and internal morphology of the oral apparatus. However, there is no evidence to support a relationship between diet and oral cavity morphology. The objective of this study was to verify if the variation in the quantity and size of the structures of the oral cavity of the tadpoles of Corythomantis greeningi and Scinax montivagus could explain the amount of the diet consumed. Also, to describe the morphology of the oral cavity of the tadpoles of these species. Nineteen tadpoles of Corythomantis greeningi and 25 of Scinax montivagus were analyzed. To verify if there is a relationship between the morphology of the oral cavity and diet, the multiple regression test was used and to verify the morphological variations in the quantity and size of the papillae along the stages of development, a correlation test was performed. The internal oral morphology was related to the diet, since a greater number of buccal floor papillae (Corythomantis greeningi) and buccal roof pustulation (Scinax montivagus) resulted in a greater amount of ingested algae. Larger and more internal oral structures were also found in later stages of development. Associations found between oral cavity papillae and pustules with diet allow us to understand a little more about the possible functions of oral cavity structures and how they are related to diet, in addition, throughout the ontogenetic developmental stages of tadpoles undergo numerous changes and understanding how they occur provides us with a broader view of the functional morphology of tadpoles.